2020
DOI: 10.30574/gscbps.2020.11.3.0185
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of fungi incidence, seed germination and aflatoxin contamination of groundnut (Arachis hypogaea L.) from Lagos, Nigeria

Abstract: Groundnut (Arachis hypogaea L.) is a legume of high nutritive and market value usually contaminated by aflatoxin. The evaluation of aflatoxin contamination of groundnut entering the food system through the markets is necessary to ascertain the quality of the groundnut sold and subsequently advice groundnut consumers. The study assessed the aflatoxin B1 (AfB1) contamination levels in groundnut sold in some markets in Lagos, Nigeria. Groundnut seeds were sampled from five Local Government Areas (L. G.A) of Lagos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…Using high performance liquid chromatography, Ifeji et al [18] analyzed raw and roasted peanuts sold in Niger state, Nigeria, and reported AFB 1 levels of 4 -188 μg/kg, while levels of 74.03 -82.12 µg kg -1 were determined for groundnuts from the Niger-Delta region in Nigeria [19], and AFB 1 levels of between 3.09 and 5.11 were detected in shelled groundnut seeds collected from five LGAs in Lagos, Nigeria [20]. Ekhuemelo and Abu, [21], sampled raw groundnut seeds stored for one to two years from six Local Government Areas (LGAs) of Benue state and evaluated them for AFB 1 using the ELISA method.…”
Section: Introductionmentioning
confidence: 99%
“…Using high performance liquid chromatography, Ifeji et al [18] analyzed raw and roasted peanuts sold in Niger state, Nigeria, and reported AFB 1 levels of 4 -188 μg/kg, while levels of 74.03 -82.12 µg kg -1 were determined for groundnuts from the Niger-Delta region in Nigeria [19], and AFB 1 levels of between 3.09 and 5.11 were detected in shelled groundnut seeds collected from five LGAs in Lagos, Nigeria [20]. Ekhuemelo and Abu, [21], sampled raw groundnut seeds stored for one to two years from six Local Government Areas (LGAs) of Benue state and evaluated them for AFB 1 using the ELISA method.…”
Section: Introductionmentioning
confidence: 99%